The American Indian and the end of the Confederacy, 1863-1866 - Abel, Annie Heloise, 1873-1947 (University of Nebraska Press, 1993)
Late in April 1861, President Lincoln ordered Federal troops to evacuate forts in Indian Territory. That left the Five Civilized Tribes-Cherokees, Chickasaws, Choctaws, Creeks, and Seminoles-essentially under Confederate jurisdiction and control. The American Indian and the End of the Confederacy, 1863-1866, spans the closing years of the Civil War, when Southern fortunes were waning, and the immediate postwar period.